WIN-WIN OR WIN LOSE? AN EXAMINATION OF CHINA’S SUPPLY OF MASS SURVEILLANCE TECHNOLOGIES IN EXCHANGE FOR AFRICAN’S FACIAL IDS (The Pretoria Student Law Review, 2023)
The use of Facial Recognition Technologies (FRT) has becomeincreasingly prevalent. While these technologies have been applaudedfor their many benefits, their use have been criticised for problemsrelating to accuracy. More particularly, FRT technologies havedemonstrated low accuracy when identifying people of colour. This hasled to the call for diversification of data, which has been intensified bymajor corporations and nations competing to lead in ArtificialIntelligence development (the AI race). In an attempt to diversify itsdata sets, China, as a significant player in the AI race, has entered intoan agreement with Zimbabwe. The agreement is meant to benefit bothparties mutually as a ‘win-win’ agreement, which entails the collectionof African facial IDs in exchange for high-end mass surveillancetechnologies. This article questions whether this agreement cangenuinely be a win-win. To demonstrate this, the article will discuss andanalyse China’s viewpoint on this ‘win-win’ in light of the AI race andtake a closer look at how this agreement places China one step ahead ofothers in the race to lead facial recognition technologies. As such, thearticle examines that which is hidden in China’s win-win perspective bydelving deeper into the biometric data and the underlying principles ofits Regulation to determine whether the collection of Facial IDs is inline with these principles. Finally, I attempt to redefine the meaning ofwhat is truly a ‘win-win’ in this context.